Love And Longing In Pre-Islamic Arabic Poetry (Al-Muʿallaqāt) - Shadeka Jannat Jannat (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This article examines the themes of love (ḥubb, ʿishq) and longing (ḥanīn, shawq) in the nasīb—the amatory prelude—of the Muʿallaqāt, the celebrated pre-Islamic odes. The objective is to understand how longing in these poems functions not only as an emotional outpouring but also as a structural, cultural, and ethical force. Methodologically, the study combines close textual readings of representative odes (Imruʾ al-Qays, Ṭarafa, Zuhayr, Labīd, and ʿAntarah) with philological analysis, reference to classical commentaries, and insights from modern scholarship in ritual poetics and oral-formulaic theory. More than twenty critical works are reviewed to situate the discussion historically and theoretically. The findings show that longing in the nasīb is not a decorative prelude but a threshold emotion: it transforms personal memory into communal values, giving credibility to later sections of the qaṣīda. Imruʾ al-Qays frames longing as knowledge, Ṭarafa ties it to mortality and generosity, Zuhayr tempers it with wisdom, Labīd elevates it into metaphysics, and ʿAntarah uses it to claim social recognition. In conclusion, love and longing emerge as the emotional engines of the Muʿallaqāt, anchoring the coherence of the qaṣīda and embodying the values of endurance, generosity, and honor.